Oxygen effect in γ-decalactone production through biotransformation of ricinoleic acid - Gomes, Nelma (2009)
γ-Decalactone can be produced biotechnologically from the degradation of ricinoleic acid by yeasts, namely Yarrowia lipolytica. Preliminary studies using two different ricinoleic acid sources (methyl ricinoleate and castor oil) at different concentrations were tested as substrates, in flask experiments. Although high amounts of γ-decalactone (up to 2 g L-1) were achieved with oil concentrations of 3% and 5% (v/v) for each substrate, the productivity of the process was small (10 to 14.5 mg L-1 h-1). In order to increase these values, essays were conducted in a 2-L bioreactor, with 3% (v/v) methyl ricinoleate at different aeration and agitation rates, in the herein presented work. Under these conditions, the highest amount of γ-decalactone achieved was lower (approximately 1 g L-1). However, the productivity of the process was much higher: 87 mg L-1 h-1. Furthermore, another compound derived from the direct precursor of γ-decalactone, 3-hydroxy-γ-decalactone, was detected in large amounts (up to 8 g L-1), which implies a change in the metabolic pathway control.